ETHICAL PRACTICES AND FINANCIAL REPORTING QUALITY OF SELECTED DEPOSIT MONEY BANKS IN LAGOS STATE, NIGERIA - Fijabi, Lateef Kolawole; Ahannaya, Chinedu Gandolph (Journal Of Islamic Finance And Accounting Research, 2025)
The absence of accounting ethics has resulted in a drop in the quality of financial reporting, which is critical for investors and management. Accountants' code of ethics, which encompasses honesty, impartiality, competence, secrecy, and professional behavior, helps to reduce the probability of misleading financial reporting. This study uses a descriptive survey research approach to assess the impact of ethical practices on the financial reporting quality of selected deposit money banks in Lagos state, Nigeria. The population consisted of employees of five listed deposit money banks in Nigeria. The result indicated that integrity, competence, objectivity, professional behavior and professional independence positively affected relevance. The result also showed that integrity, competence, objectivity, professional behavior and professional independence did not positively affect faithful representation. The result of the hypothesis one concluded that ethical practices had a significant effect on relevance. Hypothesis two concluded that ethical practices did not have a significant effect on faithful representation. Based on the findings, a few recommendations were offered on ethical practices and financial reporting quality; Measure should be made by management to ensure that ethical practices are followed to improve the performance of their organizations and to increase performance at all levels, the management team for deposit money banks should concentrate more attention on ensuring that the structure for ethical practices as it relates to financial reporting possess the required qualities.